DESIGN AND IMPLEMENTATION OF VOLTAGE AND CURRENT CONTROL FIRMWARE ON BUCK CONVERTER AND INTERFACE FOR OYIKA PORTABLE CHARGING SYSTEM - Al Fadh, Dhanurangga
ABSTRACT DESIGN AND IMPLEMENTATION OF VOLTAGE AND CURRENT CONTROL FIRMWARE ON BUCK CONVERTER AND INTERFACE FOR OYIKA PORTABLE CHARGING SYSTEM By Dhanurangga Al Fadh NIM: 13218005 ELECTRICAL ENGINEERING STUDY PROGRAM Fuel oil to electrical energy transition has become a topic that is often discussed. Many technologies have been developed to support this transition, one of which is a battery swapping system for electric vehicles, especially electric motors. The electric motor battery swapping system is currently starting to develop in Indonesia. In its development, there is a problem faced by one of the companies engaged in this field, namely Oyika. The problem is related to the existence of customers who have problems accessing the swapping station. In this final project report, Author will discuss the problem and the offered solution to this problem, namely a portable charging system. Oyika batteries cannot be charged simply by connecting the battery to a lithiun-ion battery charger sold in the market because there is a battery management system inside the battery that can regulate whether current flow. If the battery is connected directly to the charger, no current can flow into the battery, so charging cannot be carried out. This final project report discusses several subsystems of the portable charging system, namely interfaces, state control, and charger subsystems. Subsystem design includes block diagrams of each subsystem, algorithms, and components for subsystem implementation. The design of the interface subsystem considers ease of use for user. The design of the state control subsystem aims to design the control firmware so that the portable charging system can charge the Oyika battery. Then, the design of the charger subsystem focuses on controlling the output current and voltage of the charger subsystem in order to provide the appropriate charging current and voltage characteristics. Firmware implementations use the Real-Time Operating System (RTOS) to perform multiple tasks in real-time. The result of testing this system is that users can easily charge Oyika batteries using this system. Keywords: Oyika, Charger, Battery, RTOS, Interface, Control.